Landscape reshaping of the asylum of san francisco de paula, located in jaboticabal, Sao Paulo State, Brazil - Pivetta, K. F L [UNESP]; Batista, G. S. [UNESP]; Martins, T. A. [UNESP]; Coan, R. M. [UNESP]; Gimenes, R. [UNESP]; Borella, H. D. [UNESP]; Mazzini, R. B. [UNESP] (My University, 2010)
It is a commonly known fact that there are elderly who have no family or who do not receive any kind of help from their relatives, as the family does not normally have good financial conditions to help them. These elderly live in private or public shelters and generally, they do not have enough money to cover all the necessary costs, and are forced to survive from donations. Those shelters are based, primarily, on nutrition and health. Leisure and wellbeing are usually treated with little attention, but it could be obtained in a simple and effective way: green areas, which normally exist at the site, are often misused, so they can become rest areas through simple landscape projects. It is important to mention that a garden is not just a beautiful place, but it becomes important for the daily life of older people. The objective of this work was to study the need for contemplative leisure and labor in order to improve the life quality of the elderly that live at the San Francisco de Paula Asylum, in Jaboticabal City, Sao Paulo State, Brazil. In this study, a topographic and a photographic survey was conducted and an analysis of the local ground was done. The preferences of the employees and the visitors of the building were also recorded, as well as the critical points of the area. After this primary analysis, the landscape planning was done, with the help of the AutoCAD 2004 software, prioritizing the use of plants that are not dangerous and that are easy maintained. An orchid nursery was also created in order to provide weekly workshops of orchid cultivation.
Keywords: Elderly; Horticulture therapy; Landscape design; Orchid cultivation; Orchidaceae